Mouthguard use effect on the biomechanical response of an ankylosed maxillary central incisor during a traumatic impact: A 3-dimensional finite element analysis - Borges, Alexandre Luiz Souto [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; Concílio, Laís Regiane da Silva; Paes-Junior, Tarcisio José de Arruda [UNESP]; Tribst, João Paulo Mendes [UNESP] (MDPI, 2020)
(1) Background: Trauma is a very common experience in contact sports; however, there is an absence of data regarding the effect of athletes wearing mouthguards (MG) associated with ankylosed maxillary central incisor during a traumatic impact. (2) Methods: To evaluate the stress distribution in the bone and teeth in this situation, models of maxillary central incisor were created containing cortical bone, trabecular bone, soft tissue, root dentin, enamel, periodontal ligament, and antagonist teeth were modeled. One model received a MG with 4-mm thickness. Both models were subdivided into finite elements. The frictionless contacts were used and a nonlinear dynamic impact analysis was performed in which a rigid object hit the model at 1 m·s−1 . For each model, an ankylosed periodontal ligament was simulated totaling 4 different situations. The results were presented in von-Mises stress maps. (3) Results: A higher stress concentration in teeth and bone was observed for the model without a MG and with ankylosed tooth (19.5 and 37.3 MPa, respectively); the most promising mechanical response was calculated for patients with healthy periodontal ligament and MG in position (1.8 and 7.8 MPa, respectively). (4) Conclusions: The MG’s use is beneficial for healthy and ankylosed teeth, since it acts by dampening the generated stresses in bone, dentin, enamel and periodontal ligament. However, patients with ankylosed tooth are more prone to root fracture even when the MG is in position compared to a healthy tooth.
Keywords: Athletic injuries; Finite element analysis; Mouthguard; Trauma